Biogeography of cryoconite forming cyanobacteria on polar and Asian glaciers. (9th September 2017) - Segawa, Takahiro; Yonezawa, Takahiro; Edwards, Arwyn; Akiyoshi, Ayumi; Tanaka, Sota; Uetake, Jun; Irvine‐Fynn, Tristram; Fukui, Kotaro; Li, Zhongqin; Takeuchi, Nozomu
Abstract: Aim: Cryoconite, a microbe‐mineral aggregate found on glaciers worldwide, is formed by microbial phototrophs, principally cyanobacteria. Despite their ecological importance in supraglacial environments, the phylogeographical distributions of supraglacial cyanobacteria are poorly understood. Here, we investigate the biogeographical distribution of cyanobacteria on glaciers in the Antarctic, Arctic and Asia. Location: Glaciers in the Antarctic, Arctic and Asia. Methods: We analysed contiguous sequences of 16S rRNA genes and 16S–23S internal transcribed spacer (ITS) regions, determined by a long read strategy and single‐filament PCR analysis in 38 glacial samples. We analysed cyanobacterial distribution patterns and genetic differentiation. Results: The cyanobacterial 16S rRNA gene sequences were grouped into 20 operational taxonomic units (OTUs), and the six major OTUs that accounted for 88% of sequences were distributed broadly from polar to Asian glaciers, suggesting that they are cosmopolitan at the species level. However, analysis of the more variable ITS region revealed geographical differentiation at the strain level. Nineteen OTUs, including the six major OTUs, showed considerable genetic differentiation among geographical regions; at the population level, they are, thus, geographically restricted. Only one of the phylotype exhibits a population structure which does not show a relationship with geographical distribution, suggesting that is cosmopolitan, even at the strain level. Main conclusions: Our 16S rRNA gene analyses suggest a global distribution of species of cyanobacteria colonizing glacier surfaces; however, the 16S–23S ITS regions revealed that most of the phylotypes are fundamentally endemic to particular areas at the population level and indicate limited migration among regions. Our result suggests that selection pressures among geographical regions are strong driving forces shaping genetic structure in cyanobacteria.